Dynamics of the Singapore success story : insights by Ngiam Tong Dow - Zhang, Zhibin (Singapore : Cengage Learning Asia, 2011)
Based on his rich, fifty-year experience as a senior Singapore civil servant, Ngiam Tong Dow manages to present a clear picture in this book of Singapore's path toward success. It is a collection of his speeches, interviews, and articles delivered and written between 2004 and 2010. According to Ngiam, what lies behind Singapore's spectacular achievements from 1959 onward is the island nation's relentless pursuit of knowledge as the critical lever for development. Singapore is the forerunner of knowledge-based economies emerging in this new millennium
Map on lining papers.
Includes bibliographical references and index.
Keywords: Ngiam, Tong Dow; Singapore economic policy; Political planning -- Singapore; Singapore -- Economic conditions; Singapore -- Politics and government; Singapore -- Politics and government -- 1965-1990.; Singapore -- Politics and government -- 1990-